Guided Self-Help to Reduce Psychological Distress in South Sudanese Female Refugees in Uganda: A Cluster Randomised Trial - Tol A. Wietse, Leku R. Marx, Lakin P. Daniel, Adaku Alex, Mark van Ommeren (Lancet Glob Health, 2020)
Innovative solutions are required to provide mental health support at scale in low-resource humanitarian contexts. We aimed to assess the effectiveness of a facilitator-guided, group-based, self-help intervention (Self-Help Plus) to reduce psychological distress in female refugees.